2023
DOI: 10.1002/tox.23802
|View full text |Cite
|
Sign up to set email alerts
|

HDAC2 exacerbates rheumatoid arthritis progression via the IL‐17‐CCL7 signaling pathway

Abstract: Histone deacetylases (HDACs) have been reported to regulate the immune response in rheumatoid arthritis (RA). The current study aimed to explore key HDACs and their molecular mechanism in RA. First, the expression of HDAC1, HDAC2, HDAC3 and HDAC8 in RA synovial tissue was determined by qRT‐PCR. The effects of HDAC2 on the proliferation, migration, invasion, and apoptosis of fibroblast‐like synoviocytes (FLS) in vitro were studied. Furthermore, collagen‐induced arthritis (CIA) rat models were established to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…3 B, Table S4 ). Notably, among these pathways, the top-ranked in relation to RA was the IL-17 signaling pathway, which has been reported to aggravate RA when activated [ 26 ]. This process involves the expression of IL-17, NF-κB, and MMP [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…3 B, Table S4 ). Notably, among these pathways, the top-ranked in relation to RA was the IL-17 signaling pathway, which has been reported to aggravate RA when activated [ 26 ]. This process involves the expression of IL-17, NF-κB, and MMP [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, only one case-control study was found to observe significantly elevated MCP-3/CCL7 levels in the serum of AS patients ( 46 ), but further studies between the two were lacking.MCP-3/CCL7 is a chemokine that attracts monocytes during inflammation and metastasis. MCP-3/CCL7 was found to be involved in the IL-17 signaling pathway, and overexpression of MCP-3/CCL7 exacerbates the progression of RA ( 47 ). Therefore, inhibition of the IL-17-CCL7 signaling pathway may be a promising therapeutic target for RA.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, those inhibitory effects of SCFAs on HDAC activity is not limited to immune cells in the intestine, but also extends to other tissues and organs through the circulation. The inhibition of HDACs leads to the inactivation of NF-κB, which subsequently reduces the release of inflammatory cytokines in RA patients and arthritic mice (Kim et al, 2018;Mao et al, 2023;Vijaykrishnaraj et al, 2023).…”
Section: Scfasmentioning
confidence: 99%